COMPLIANCE OF ANTI-SMOKING REGULATIONS BY CIGARETTE INDUSTRY IN PAKISTAN - Rasool, Ahsan; Ahmad, Shehraz; Farooq, Umer; Rasool, Maleeha; Shah, Zahika; Hammad, Muhammad; Utmanzai, Ashfaq; Wahab, Fazli; Sadique, Irum; Ahmad, Jawad (Journal of Ayub Medical College Abbottabad, 2011)
Background: The hazards of cigarette smoking and its increasing consumption are well known despite the ongoing tussle between the tobacco industry and global governments. To curb the menace of smoking, anti-smoking laws have been enforced from time to time by various governments. In 2003, Ministry of Health (MoH) Government of Pakistan has imposed certain regulations on cigarette manufacturing industry. The aim of this study was to highlight the compliance of the industry with these regulations. Methods: A cross-sectional study of major cigarette selling shops was conducted in Abbottabad. It was aimed at determining the availability of total cigarette brands and their compliance with the regulations and also to find out attributes of cigarette customers. Results: A total of 39 varieties of 18 cigarette brands are available in Abbottabad city, out of which 71.8% are imported varieties. A total of 38.4% varieties have displayed health warnings (28.2% pictorial health warning, 10.2% have written health warning. Majority of cigarette customers are between 20-40 years of age, while 5.6% customers include youngsters between 10-20 years of age. Female customers, accounting for 8% of total cigarette customers, buy only those brands which have not displayed the health warning. Conclusions: Observed compliance with governmental regulation for displaying health warning is 39% which is far less than desired. Sale of cigarette to children is also practiced. Ministry of Health (MoH) should assure the display of these warnings on all the brands so that smokers must be fully aware about the risk involved in smoking Keywords: Cigarette smoking; anti-smoking regulations; protection of non-smoker health.